2015
DOI: 10.1002/hbm.23047
|View full text |Cite
|
Sign up to set email alerts
|

Heritability of complex white matter diffusion traits assessed in a population isolate

Abstract: Introduction Diffusion weighted imaging (DWI) methods can non-invasively ascertain cerebral microstructure by examining pattern and directions of water diffusion in the brain. We calculated heritability for DWI parameters in cerebral white (WM) and gray matter (GM) to study the genetic contribution to the diffusion signals across tissue boundaries. Methods Using Old Order Amish (OOA) population isolate with large family pedigrees and high environmental homogeneity, we compared the heritability of measures de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
3
22
1
Order By: Relevance
“…Notably reduced sagittal stratum FA was shown to be genetically associated with processing speed deficits in two independent cohorts. 11 We previously observed a decrease in processing speed in U-2 pilots compared to a USAF pilot control cohort 19 and, thus, this may suggest the reduced sagittal stratum FA in U-2 pilots may explain this decrease in processing speed. Additionally, USAF pilots are uniquely high-functioning individuals with exceptional visual-spatial abilities, 3 which may account for the higher FA values in the fronto-occipital fibers in U-2 pilots, reflecting this associative cognitive ability, and provide an anatomical basis for the superior spatial performance noted in all USAF pilots.…”
Section: Discussionmentioning
confidence: 83%
“…Notably reduced sagittal stratum FA was shown to be genetically associated with processing speed deficits in two independent cohorts. 11 We previously observed a decrease in processing speed in U-2 pilots compared to a USAF pilot control cohort 19 and, thus, this may suggest the reduced sagittal stratum FA in U-2 pilots may explain this decrease in processing speed. Additionally, USAF pilots are uniquely high-functioning individuals with exceptional visual-spatial abilities, 3 which may account for the higher FA values in the fronto-occipital fibers in U-2 pilots, reflecting this associative cognitive ability, and provide an anatomical basis for the superior spatial performance noted in all USAF pilots.…”
Section: Discussionmentioning
confidence: 83%
“…The corpus callosum is strongly implicated in a variety of sex-linked genetic disorders including supernumerary sex chromosome aneuploidies (Wade et al, 2014) and Fragile X syndrome (Villalon-Reina et al, 2013), as well as many other complex neuropsychiatric disorders ranging from major depressive disorder (Ballmaier et al, 2008), bipolar disorder (Fears et al, 2014) and schizophrenia (Narr et al, 2000, Kochunov et al, 2014), to various types of dementia (Daianu et al, 2015), and many others. Not only is it implicated in these numerous diseases with sex differences in their prevalence, it is also highly genetically influenced (Bearden et al, 2011, Jahanshad et al, 2013, Kochunov et al, 2016). More practically, unlike some other structures with widely reported structural and functional sex differences, like the amygdala (Hamann, 2005), the corpus callosum is simple to extract and measure from many modalities of neuroimaging; given the controversy in findings, a structure that is easier and more reliable to measure (Morey et al, 2010) might be a good target to analyze, and methodological errors in its measurement are perhaps less likely to influence the reported sex differences.…”
Section: Introductionmentioning
confidence: 99%
“…Chiang et al [] reported that the voxel‐wise heritability of FA in some tracts was greater in adolescents (around 70%–80%) compared with young adults (around 30%–40%), which might suggest that the heritability of FA could be even lower in older adults. Although some family studies have included older participants [Bertisch et al, ; Kochunov et al, ; Skudlarski et al, ], the samples had very wide age ranges, thus their reported heritabilities are not particularly informative about whether FA heritability is lower in older versus younger samples. One family study directly tested the association of age to genetic influences within their study sample, but did not find any interactions between age and genetic effects on global or tract specific FA [Glahn et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Whether they are also similar to each other in adults is less clear. In two samples of adults of a wide age range, Kochunov et al [] reported overall heritabilities of 37% and 72% for RD, and nonsignificant 9% and 41% for AD. Kanchibhotla et al [] examined the corpus callosum in older adults and reported heritabilities of 49% for RD and 37% for AD.…”
Section: Introductionmentioning
confidence: 99%